Three amigos! [videorecording (DVD)] - Martin, Steve, 1945-; Martin, Steve, 1945-; Chase, Chevy; Short, Martin, 1950- (HBO Home Entertainment, 2011)
The Three Amigos, a silent screen comedy act, arrive in a remote Mexican hamlet for what they think is a lucrative personal appearance, only to discover that they are expected to save the village from a terrorizing gang of bandits.